A contribution to the study of Newcastle disease congenital immunity in chickens - Silva, Milton Marques da; Brada, Wilhelm (Pesquisa Agropecuaria Brasileira, 2014)
The presence of congenital antibodies of Newcastle disease (DNC) in serum and in the vitelline sac of newborn chickens was investigated. It was found that the decrease of DNC antibodies present in serum starts after the 7th day of life and in the vitelline sac the decrease occurs after the 5th day. In chickens with congenital immunity, inoculated with attenuated virus vaccine, the content of inhibiting antibodies was higher when inoculated after the 8th day and lower when inoculation was made during the first days of life.